Makna Visual Karakter Denmas Aria Kendor dalam Komik Strip Panji Koming dengan Pendekatan Ikonograf - Hedi Hadiansyah (Pascasarjana ISBI Bandung, 2021)
Denmas Aria Kendor is one of the characters in Panji Koming’s comic strip which is periodically published by Kompas newspaper on Sunday. His roles are both as the one opposed to the character of Koming and Pailul and the one who delivers an opinion and messages through that comic strips. Denmas Aria Kendor have distinctive visual image so it becomes easily recognized and symbolizes certain meaning. The purpose of this research is to interpret the visual image of Denmas Aria Kendor in Panji Koming’s comic strip, especially seen from the physical features, posture, pose, expression and gesture. This research applies the iconography analysis method on the character design and body language of Panji Koming comic strip. This study reveals the character of Denmas Aria Kendor’s character. He is the character reflecting the government official image with superior attitudes. Keywords: Denmas Aria Kendor, Visual Meaning, Comic Strip Panji Koming, Iconography